Developing key indicators for sustainable food system: a comprehensive application of stakeholder consultations and Delphi method - Rittirong, Jongjit; Chuenglertsiri, Pattraporn; Nitnara, Pimolpan; Phulkerd, Sirinya (Frontiers in Sustainable Food Systems, 2024)
The overall status of the food system in Thailand is currently unknown. Although several national and international reports describe Thailand food system, they are not accurate and relevant to inform policies. This study aims to develop indicators which measure Thailand's sustainable food system. We adopted seven-dimensional metrics proposed by Gustafson to facilitate a comparative analysis of food systems, namely (1) food nutrient adequacy; (2) ecosystem stability; (3) food availability and affordability; (4) sociocultural well-being; (5) food safety; (6) resilience; and (7) waste and loss reduction. Three rounds of the Delphi method were convened to assess the proposed indicators using the Item Objective Congruence (IOC) by 48 Thai stakeholders recruited from the government, NGOs, and academia. IOC is a procedure used in test development for evaluating content validity at the item development stage. In each round, the average IOC for each item was carefully considered, together with stakeholders' comments on whether to retain, remove, or recruit new indicators. The communication through mail and email was sent out so that stakeholders could assess independently. A total of 88 and 73 indicators went to the first and second round Delphi assessment; this resulted in 62 final indicators after the third round. In conclusion, these 62 indicators and 190 sub-indicators are too many for policy uses. As an ongoing indicator development, we plan that these 62 indicators will be further tested in different settings to assess data feasibility. After field tests, the final prioritized indicators will be submitted for policy decisions for regular national monitoring and informing policy towards sustainable food systems in Thailand.